Assessing the spatiotemporal variability of urban heat island and thermal comfort in Greater Francistown City - Kudoma, Bongayi (University of the Witwatersrand, Johannesburg, 2024)
Climate change and global warming have increased land surface temperature (LST) in urban areas, causing urban heat islands (UHI), affecting residents' thermal comfort. The UHI effect in Greater Francistown City is causing temperatures to rise, potentially affecting residents' thermal comfort. The study combined remote sensing and statistical techniques to collect Landsat-8 OLI/TIRS-1 data and analyses spatiotemporal variability of LST, vegetation, built-up areas, UHI phenomenon and thermal comfort levels in the city from 2014-2023. Results revealed that built-up areas covered 59.02% of the City in 2023, reducing vegetation to 33.26% and affecting thermal comfort. UHI effects have grown due to LST variations near bareland and built-up areas. Urban hotspots increased, peaking at 3.12% in 2023, with thermal comfort levels varying between 2016 and 2023. Expanding the built-up regions, reduced vegetation, land-cover changes contributed to the UHI effects and changes in thermal comfort patterns. Recommending sustainable urban planning to improve urban liveability.
Research report submitted in fulfilment of the requirements for the Degree Master of Science in Geographical Information Systems and Remote Sensing, Faculty of Science, School of Geography, Archaeology and Environmental Studies, University of the Witwatersrand, Johannesburg, 2024
Keywords: Urban Thermal Field Variance Index; Thermal Comfort; Land surface temperature; Urban Heat Island; Landsat 8 OLI/TIRS; Francistown City; Botswana; UCTD; SDG-13: Climate action; SDG-15: Life on land